BANGKOK TOURISM NETWORK COMMUNICATION FRAMEWORK DEVELOPED FROM THE PROTOTYPE OF THE ZURICH TOURISM NETWORK SWITZERLAND - Suacharoen, Kidudom; Boonsiri, Karn; Torkaew, Wittayatorn; Ngamsanit, Sman (Journal of Social Science and Cultural, 2024)
This research aims to investigate: 1) The communication management patterns of the Zurich Tourism Network, Switzerland 2) The problems and communication management needs of the Bangkok tourism network 3) Develop a proposal for a communication management model for the Bangkok tourism network based on the model used in the Zurich Tourism Network, Switzerland. The research is qualitative in nature and involves in-depth interviews with two main groups of key informants: 1) leaders and experts in the Zurich tourism network, Switzerland; and 2) leaders and experts in the Bangkok tourism network. Data analysis is conducted by generating conclusions. The research findings: 1) The communication management pattern in Zurich Tourism network, Switzerland, can effectively establish and maintain network relationships. This is achieved through a network structure that links all components equally, guided by policies, missions, plans, and appropriate communication practices. Regular communication assessments ensure consistency. The network emphasizes principles of integrity and transparency, considering mutual benefits. 2) The problems and communication management needs of The Bangkok tourism network are characterized by a lack of clear policies, missions, plans, and communication practices. This results in an unsuitable communication environment, with a lack of alignment between organizational units. Communication assessments are error-prone, hindering the creation and maintenance of effective network relationships. 3) The proposal suggests that all sectors should collaboratively establish unified policies, missions, plans, and communication practices aligned with the context of tourism in Bangkok. This collaborative effort aims to create and maintain sustainable network relationships. The emphasis is on creating a network structure that promotes collaboration, ensuring long-term mutual cooperation among sectors. The main outcome is the PARTNER Communication model for tourism network management, consisting of seven components, aiming for maximum efficiency in networking for tourism, enhancing competitiveness, and adaptability for future use in other organizations.